2019
DOI: 10.1891/1946-6560.10.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Controlling Behaviors in Adolescent and Youth Intimate Partner Relationships

Abstract: Considerable evidence shows that adolescent intimate relationships influence the course of adult relationships, that is, whether relationship experiences are characterized by abuse or violence, or healthy, equitable dynamics. Controlling behaviors (CBs)—a phenomenon related to intimate partner violence (IPV)—are pervasive in adolescent intimate relationships, yet there is a lack of consensus on how to conceptualize them and subsequently, limited research which explores the role of CBs, including their role as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…These authors' discourse analysis of these applications revealed the same dichotomy identified by the literature and by 12 of the 14 participants in this study, which equates tracking and control with caring and love. In this vein, Taylor et al (2019) argue that controlling behaviors via technological means is present in the intimate relationships of most young Brasilians and that their overt use might indicate "collaboration" between partners as a strategy to prevent escalation of conflicts involving fears of infidelity and jealousy. In keeping with this analysis, one Brasilian participant from the legal sector emphasized that a common practice among young Brasilians is to create a shared account on social media as soon as they start dating as a way to keep track of each other (see also Campeiz, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These authors' discourse analysis of these applications revealed the same dichotomy identified by the literature and by 12 of the 14 participants in this study, which equates tracking and control with caring and love. In this vein, Taylor et al (2019) argue that controlling behaviors via technological means is present in the intimate relationships of most young Brasilians and that their overt use might indicate "collaboration" between partners as a strategy to prevent escalation of conflicts involving fears of infidelity and jealousy. In keeping with this analysis, one Brasilian participant from the legal sector emphasized that a common practice among young Brasilians is to create a shared account on social media as soon as they start dating as a way to keep track of each other (see also Campeiz, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The scarcity of examples of healthier relationships might hinder young people's identification of what is acceptable or not (Taylor et al, 2019). Taylor et al (2019) indicate that, while many young Brasilians do not identify control as abuse, they often said they did not like it.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations